Outcomes of bariatric surgery in elderly patients: A registry-based cohort study with 3-year follow-up. (1st June 2022) - Iranmanesh, P; Boudreau, V; Anvari, M
Abstract: Objective: Elderly patients undergo bariatric surgery less frequently than younger patients. Short- and medium-term outcomes after bariatric surgery in the elderly population remain largely unknown. The objective of the present retrospective, registry-based cohort study was to compare short- and medium-term outcomes between patients <65 and ≥65 years undergoing bariatric surgery, hypothesizing similar outcomes between groups. Methods: In this retrospective, registry-based cohort study, the Ontario Bariatric Registry was used to compare data of patients <65 and ≥65 years who underwent Roux-en-Y gastric bypass and sleeve gastrectomy between January 2010 and August 2019 in all accredited bariatric centers of excellence in Ontario, Canada. Primary outcomes were overall postoperative complications. Secondary outcomes included early (<30 days) complications, readmissions, reoperations, mortality, weight loss and comorbidities improvement at 1 and 3 year after surgery. Results: Data of 22, 981 patients <65 and 532 patients ≥65 years were analyzed. Overall postoperative complications were similar between patients <65 and ≥65 years (3388/22, 981 [14.7%] vs. 73/532 [13.7%], p = 0.537). Early (<30 days) postoperative complications, readmissions, reoperations, and mortality rates were also similar between groups. Both groups had significant weight loss and comorbidities improvement at 1- and 3-year follow-up. Patients <65 years had superior weight loss (+3.5%, 95% CI: 1.6–5.4, p < 0.001) and higher rates of remission for diabetes mellitus (63.8% vs. 39.3%, p < 0.001), hypertension (37.9% vs. 14.5%, p < 0.001), dyslipidemia (28.2% vs. 9.5%, p < 0.001) and gastroesophageal reflux (65.1% vs. 24.0%, p < 0.001) compared to patients ≥65 years at 3 year. Conclusion: Patients <65 and ≥65 years had similar perioperative morbidity and mortality after bariatric surgery. Even though patients <65 years had overall better medium-term outcomes, bariatric surgery is safe and yields significant weight loss and comorbidities improvement in patients ≥65 years.